TATA KELOLA PERUSAHAAN (CG) DAN TINGKAT INOVASI PERUSAHAAN - Bayu Sindhu Raharja; Nur Laila Yuliani (Universitas Muhammadiyah Metro Lampung, 2019)
This study examines the relationship between corporate governance in explaining the level of innovation of the company. The sample in this study uses companies that have a high level of liquidity in stock trading after the authoritarian era of the